Evaluation of the Effectiveness of the Internal Control System in the Implementation of the Centralized Payment Digitalization Program at UIP3B PLN Sulawesi - Aini Indrijawati; Mediaty Mediaty; Mursandi Mursandi; Nurazizah Nurazizah; Nurul Azizah Tamang; Tahlis Farida Novianti (Transpublika Publisher, 2026)
Digital transformation in the financial sector requires organizations to enhance their digital maturity to effectively manage systems efficiently and transparently. This study aims to evaluate the level of organizational digital maturity through the implementation of the Digitalization of Centralized Payment program at PT PLN (Persero) UIP3B Sulawesi, and to analyze the effect of payment digitalization on the effectiveness of internal control systems with human resource (HR) competence as a mediating variable. This study employs a quantitative approach with an explanatory research design. Primary data were collected through online questionnaires distributed to 78 employees in the finance and budgeting departments who were directly involved in the centralized payment digitalization program. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The research findings indicate that payment digitalization has a positive and significant effect on HR competence and the effectiveness of internal control systems. Furthermore, HR competence was proven to function as a partial mediator in the relationship between payment digitalization and internal control effectiveness, with t-statistic values > 1.96 and p-values < 0.05. All variable indicators have loading factors > 0.7 and Composite Reliability > 0.8, indicating valid and reliable research instruments. Thus, it can be concluded that enhancing HR competence is a key factor in strengthening the effectiveness of internal control systems through the successful implementation of centralized payment digitalization. These results emphasize the importance of developing human capabilities as an integral part of digital transformation within the UIP3B PLN Sulawesi environment.